Body composition, dietary intake and supplement use among triathletes residing in the Western Cape Region - Bam, Sunita (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr(Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.